Tourists’ demographics and consumer behavior: Unveiling differences in culinary tourism - Ramon Hurdawaty; Wirawan Dony Dahana; Yuary Farradia (Universitas Ahmad Dahlan, 2025)
Culinary tourism has gained increasing attention as destinations seek to create memorable travel experiences. This research addresses a gap in the literature regarding how tourist demographics shape memorable culinary experiences and revisit intention. The study's main objective is to analyze the differences in tourists' demographic attributes, including age, gender, culinary expenditure, and culinary preferences, concerning their perceptions and intentions. The research used quantitative methods through a survey analysis of 400 domestic tourists in Magelang, Central Java, Indonesia. The impact of demographic differences was calculated using ANOVA and an independent-sample t-test with SPSS version 24. The results show that age and culinary expenditure differentiate the perception of memorable culinary tourism experiences. In contrast, no significant differences were found between the demographic variables of gender and culinary tourism preference. Moreover, no significant differences were found in tourists’ perceptions of revisit intention across any demographic variables. These findings suggest that tourism managers and policymakers adopt a dual strategy: designing memorable and emotionally engaging culinary experiences across all groups while shifting from demographic-based targeting to psychographic and experiential segmentation. This study contributes to a better understanding of consumer behavior in culinary tourism and provides practical insights for destination management and policy development.